Datalog Reloaded First International Workshop, Datalog 2010, Oxford, UK, March 16-19, 2010. Revised Selected Papers - Moor, Oege.; Gottlob, Georg; Furche, Tim.; Sellers, Andrew; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the thoroughly refereed post-workshop proceedings of the First International Workshop on Datalog 2.0, held in Oxford, UK, in March 2010. The 22 revised full papers presented were carefully selected during two rounds of reviewing and improvements from numerous submissions. The papers showcase the state-of-the-art in theory and systems for datalog, divided in three sections: Properties, applications, and extensions of datalog.
Keywords: Computer science; Computer Communication Networks; Software engineering; Information storage and retrieval systems; Artificial intelligence; Computer Science; Information Systems Applications (incl. Internet).; Computer Communication Networks; Information Storage and Retrieval; Artificial Intelligence (incl. Robotics).; Software Engineering; Mathematical Logic and Formal Languages